PROLACTIN AS AN IMMUNOMODULATOR IN RHEUMATIC DISEASES: THE POTENTIAL ROLE OF PHYSICAL EXERCISE IN THE PROLACTIN-IMMUNE AXIS - Kuś, Monika; Słomkowski, Grzegorz; Kuśmierowska, Natalia Sara; Polak, Milena; Karolak, Dominika; Białowąs, Tymoteusz; Wiśniewski, Konrad; Nowak, Magdalena; Cholewiński, Kacper; Valipur Kolti, Daria (International Journal of Innovative Technologies in Social Science, 2026)
Background and Objectives. Prolactin (PRL) is produced by pituitary and extra-pituitary tissues and signals via the prolactin receptor (PRLR), a class I cytokine receptor that activates pathways such as JAK2/STAT5, supporting a cytokine-like role in immune regulation [1-3]. Exercise and heat stress can transiently increase PRL and may confound interpretation in rheumatology [4-6]. We review PRL/PRLR evidence across systemic autoimmune rheumatic diseases and discuss implications for PRL testing around physical activity.Materials and Methods. Narrative review of PubMed/MEDLINE and PubMed Central (inception–15 February 2026) using terms related to PRL/PRLR, systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), Sjögren’s syndrome (pSS), exercise and heat stress. Evidence was synthesized qualitatively given heterogeneity in assays, sampling and outcomes. Macroprolactin and analytical interference were considered as key confounders [1, 7, 8].Results. Associations between mildly elevated PRL and disease activity were most consistent in SLE, supported by observational studies and syntheses, while interventional data with dopamine agonists remain limited and heterogeneous [9-11]. Findings in RA and pSS were more variable, with stronger signals for local PRL/PRLR relevance than for serum PRL as a universal biomarker [12, 13]. Acute vigorous exercise and passive heat exposure can raise PRL, potentially mimicking disease-related hyperprolactinemia if sampling is not standardized [4, 5, 14, 15].Conclusions. PRL is a plausible neuroendocrine-immune modulator in rheumatic disease, particularly SLE [11, 16, 17]. Exercise should not be restricted on PRL grounds, but PRL testing should be standardized relative to recent exertion and thermal stress [5, 14, 15, 18].